Characterizing clinical patterns of physical therapy activities for post-stroke spasticity in stroke rehabilitation: looking into the “Black Box” - Afzal, Binash; Rabiya Noor (Journal of the Pakistan Medical Association, 2024)
Physical therapy is considered to be an adjunctive therapy for the management of post-stroke spasticity. The insight of this study is to observe the current clinical practices of rehabilitation for post-stroke spasticity. For this purpose, an observational cross-sectional study was conducted. Data was collected by a standardized therapy documentation form for spasticity management. Fifty physiotherapists filled out that form. Almost all of them used subjective measures (modified Ashworth scale) for spasticity assessment and functional independence measure for level of independence. Readings were taken in the first, second, and third blocks of six-hour duration. Results showed that 42 (83.5%) physiotherapists measured spasticity at the initial session, while 47(94.6%) reported various multiple rehabilitation treatment preferences for spasticity management. Disparities exist in therapeutic management for post-stroke spasticity throughout rehabilitation which are mainly based on physiotherapists’ clinical expertise. —Continue